2002
DOI: 10.1302/0301-620x.84b7.13094
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative measurement of knee kinematics in reconstruction of the anterior cruciate ligament

Abstract: Our objectives were to establish the envelope of passive movement and to demonstrate the kinematic behaviour of the knee during standard clinical tests before and after reconstruction of the anterior cruciate ligament (ACL). An electromagnetic device was used to measure movement of the joint during surgery. Reconstruction of the ACL significantly reduced the overall envelope of tibial rotation (10 degrees to 90 degrees flexion), moved this envelope into external rotation from 0 degrees to 20 degrees flexion, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 16 publications
5
111
0
5
Order By: Relevance
“…Increased anterior tibial translation without significant difference in knee rotation during pivot shift test in ACL deficient knee was previously demonstrated using non-invasive electromagnetic system [17] and reaffirmed by the other measurement system in which the sensors were fixed to the bones [4,10]. Kanamori et al [19] detected the rotational angle change as well as increased anterior tibial translation against pure rotational loading in ACL deficient knees by use of robotic system, but the rotational angle difference was so small that they suggest the coupled anterior tibial translation for evaluating ACL function [19].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Increased anterior tibial translation without significant difference in knee rotation during pivot shift test in ACL deficient knee was previously demonstrated using non-invasive electromagnetic system [17] and reaffirmed by the other measurement system in which the sensors were fixed to the bones [4,10]. Kanamori et al [19] detected the rotational angle change as well as increased anterior tibial translation against pure rotational loading in ACL deficient knees by use of robotic system, but the rotational angle difference was so small that they suggest the coupled anterior tibial translation for evaluating ACL function [19].…”
Section: Discussionmentioning
confidence: 63%
“…The variation of the resultant knee kinematics is highly expected by manual pivot shift tests [10,34]. The magnitude of the pivot shift could be varied depending on the maneuver, such as hip position [3], applied rotational stress [20] and axial compression, and each knee has individually different loading condition to exert the maximum pivot shift [9,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While uncoupled rotation may not be significantly different after isolated rupture of the ACL [17], it has been shown that more complex tests such as the flexion rotation drawer or pivot shift tests will be positive [18]. Bull et al [11] intended to quantify the motion that occurs with reduction of the pivot shift and reported a combination of posterior translation and external rotation in 80% of their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Electromagnetic tracking systems also have high reported accuracy of <0.3% of the distance between the sensors and <1.0° [10]. These systems have been successfully used to describe kinematics, such as during a pivot shift test [11,12]. However, placing electromagnetic sensors on the skin produces undesired artifacts and can lead to measurement inconsistencies [13,14].…”
Section: Introductionmentioning
confidence: 99%